Tinjauan Pustaka Sistematis: Model Kemitraan antara SMK dengan Dunia Usaha dan Dunia Industri - Soleh, Ali Ahmadi; Triyanto, Triyanto; Parno, Parno; Suharno, Suharno; Estriyanto, Yuyun (JIPTEK: Jurnal Ilmiah Pendidikan Teknik dan Kejuruan, 2023)
Vocational education has a very important role in the national education system to create a quality national workforce. One of the programs to increase the absorption of SMK graduates in industry is the existence of a partnership program between SMKs and the Business and Industrial World (DUDI). Based on 19 articles published in 2018-2022 concerning partnerships between SMKs and DUDI, several partnership models have been established, including curriculum alignment based on industry needs, teacher and student apprenticeships, guest teachers from industry, industrial visits, teaching factory assistance, testing competency certification, employee recruitment, and infrastructure support. Some of the obstacles and challenges encountered, namely the partnership program has not been implemented optimally, the work unit is not suitable, the contents of the memorandum of understanding (MoU) have not been fully realized, the form of partnership activity is unclear, lack of concern for both SMK and DUDI in implementing the partnership program, and competition between industry causes a lack of industry trust to involve students in the production process. While the opportunities that exist include the involvement of Vocational Schools in the production process through Teaching Factory, technology updates, student competency according to industry needs and the absorption of graduates by industry is increasing.